2019
DOI: 10.25095/mufad.625790
|View full text |Cite
|
Sign up to set email alerts
|

Kripto Para Piyasasında Spekülatif Fiyat Balonlarının Analizi

Abstract: Kripto para birimi fiyatlarının tartışmalı yükselişi, bu varlıkların finansal sistemin geleceğindeki rolü ile ilgili görüşleri kutuplaştırmıştır. Piyasa etkinliğine dair en kritik göstergelerden birisi olan fiyat balonları, piyasanın geleceğine dair yapısal ipuçları taşımaktadır. Bu çalışmanın amacı, dünya çapında kripto-borsalarda işlem gören kripto para birimlerinde spekülatif fiyat balonlarının varlığını araştırmaktır. Bu amaçla piyasada en çok işlem gören 8 kripto para biriminde spekülatif fiyat balonların… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…Finally, while 70 price bubbles were detected for Binance Coin before COVID-19, 139 price bubbles were detected after COVID-19. At this point we differ with the study of Güleç and Aktaş (2019). Additionally, this result have demonstrated that cryptocurrencies are an asset with high risks and are highly sensitive to speculative movements.…”
Section: Data and Econometric Analysiscontrasting
confidence: 57%
“…Finally, while 70 price bubbles were detected for Binance Coin before COVID-19, 139 price bubbles were detected after COVID-19. At this point we differ with the study of Güleç and Aktaş (2019). Additionally, this result have demonstrated that cryptocurrencies are an asset with high risks and are highly sensitive to speculative movements.…”
Section: Data and Econometric Analysiscontrasting
confidence: 57%